Modification of a pulsed 14-MeV fast neutron generator to a medium-energy ion accelerator for TOF-RBS application - P. Junphong (2018)
The first drift-tube neutron generator in Thailand, developed during 1980s under the support by the International Atomic Energy Agency (IAEA), was a 150 kV deuteron accelerator-based 14 MeV fast neutron generator. The accelerator was featured by a nanosecond pulsing system consisting of a beam chopper in combination with a beam buncher. Following the rapid development of ion beam technology and increasing needs for materials applications in the laboratory, the accelerator has been upgraded and modified to a large extent into a medium-energy ion-accelerator for time-of-flight Rutherford backscattering spectrometry (TOF-RBS) applications. The modification of the accelerator included the changing of the ion source, the accelerating tube and the mass-analyzing magnet, the upgrading of the pulsing system, and the installation of a TOF-RBS detecting system. The new accelerator is capable of supplying a 400-keV He-ion beam with ns-pulses for nano-layered materials analysis. This paper provides technical details of the modification. © 2011 Elsevier B.V. All rights reserved.